Comparison of executive functions in Russian and Japanese preschoolers - Veraksa, Aleksander; Hasegawa, Mari; Bukhalenkova, Daria; Almazova, Olga; Aslanova, Margarita; Matsumoto, Emi (Frontiers in Psychology, 2024)
This study analyzed differences in level of main executive function (EF) components (such as inhibition, working memory and cognitive flexibility) among Russian and Japanese preschoolers. The study involved 102 children of 5 to 6.9 years old: 51 child from Russia and 51 child from Japan. Out of 102 children 48 were boys and 54 girls. It was found that the cognitive flexibility level in Russian children is higher and inhibition level is lower than in Japanese children. The results of the boys' EF comparison showed that boys from Russia have lower cognitive and physical inhibition levels than boys from Japan. Also it was shown that cognitive flexibility in Russian girls is significantly higher and cognitive inhibition is lower than in Japanese girls. The results obtained are discussed from the point of view of possible cultural differences in the two countries studied, which are manifested in the expectations of adults from children.